Une Église missionnaire par nature, et donc " synodale ": Réflexions pour la suite du Synode sur la synodalité - Eychenne, Jean-Marc (Nouvelle revue théologique, 2024)
As a member of the 16th Ordinary General Assembly of the Synod of Bishops devoted to synodality, the Bishop of Grenoble examines the missionary dimension constitutive of the synodal style of life to which the Church is committed today. He re-reads the Vatican ii decree Ad gentes and examines the conditions in which it was drawn up. He can then clarify the necessary link between the mission of human promotion and the spiritual mission, between the service of the poor and the worship of God, between human happiness and the glory of God, which characterises the very life of the Church.